2018
DOI: 10.1007/s00270-018-1912-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting a Good Symptomatic Outcome After Prostate Artery Embolisation (PAE)

Abstract: Both the initial prostate size and percentage volume reduction at 3 months predict good symptomatic outcome at 12 months. These findings therefore aid patient selection and counselling to achieve optimal outcomes for men undergoing prostate artery embolisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 19 publications
3
33
0
2
Order By: Relevance
“…The effect of PAE on ejaculatory function was reported by 11 of the reviewed studies. There were no instances of retrograde ejaculation in 5 cohort studies totaling 340 patients (39,41,43,44,46,48), 1 cohort (34) reported 5 of 51 cases with dry or reduced ejaculation after PAE, and another cohort (35) showed reduced ejaculation in 14 of 97 patients. In the prospective UK-ROPE registry (32), 24.1% of patients reported retrograde ejaculation following PAE; however, the data were confounded by many patients having preexisting retrograde ejaculation related to medical therapy.…”
Section: Safety Of Paementioning
confidence: 99%
See 2 more Smart Citations
“…The effect of PAE on ejaculatory function was reported by 11 of the reviewed studies. There were no instances of retrograde ejaculation in 5 cohort studies totaling 340 patients (39,41,43,44,46,48), 1 cohort (34) reported 5 of 51 cases with dry or reduced ejaculation after PAE, and another cohort (35) showed reduced ejaculation in 14 of 97 patients. In the prospective UK-ROPE registry (32), 24.1% of patients reported retrograde ejaculation following PAE; however, the data were confounded by many patients having preexisting retrograde ejaculation related to medical therapy.…”
Section: Safety Of Paementioning
confidence: 99%
“…The other 16 unique cohort studies at different institutions all reported similar positive outcomes in terms of efficacy and safety. Considering the 7 cohort studies of PAE with 25 or more patients and 1 year or longer follow-up (35,40,41,43,44,48,50), mean IPSS improvement ranged from 11.2 to 18.0 points and QOL improvement ranged from 1.9 to 4.7 points. Technical success rates were 93.2%-100% for unilateral embolization and 86.3%-97.4% for bilateral embolization.…”
Section: Cohort Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome predictors of PAE have barely been investigated and conflicting results require elucidation. The aim of the present study was to assess the variability of treatment outcomes in a patient cohort undergoing PAE within a randomized, open‐label, non‐inferiority trial and to identify patient characteristics and findings related to the intervention that might allow improved patient selection and early estimation of PAE outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Questions that need to be addressed in the future include the appropriate spectrum of patients and indications for PAE. Though larger prostate volumes have been reported to be associated with a more successful outcome, little is known about outcome prediction and predisposing factors for treatment success or failure [32][33][34]. Considering its minimal invasiveness and the advantages addressed above, PAE may not only be considered as a substitute for invasive treatment of BPH-LUTS but also for medical treatment.…”
Section: Discussionmentioning
confidence: 99%